EMPIRICAL ASSESSMENT ON ADOPTION OF TANUVAS SMART MINERAL MIXTURE BY THE DAIRY FARMERS OF TAMIL NADU - S. Karthikeyan; N. Narmatha; V. Uma; K. Sivakumar; G. Kumaresan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was undertaken to understand the present status of adoption of TANUVAS SMART mineral mixture, viz, complete adoption, partial adoption, discontinuance and rejection and its perceived attributes, namely, relative advantage, compatibility, complexity, observability and trialability using the schedule developed for the purpose and the economic impact. Partial budgeting was done to assess the economic impact of adopting TANUVAS SMART mineral mixture. Personal cosmopolite and personal localite communication channels had contributed majorly to the awareness of the dairy farmers followed by mass media. Majority of the dairy farmers (78%) discontinued the adoption of the innovation. Sixty six per cent of them had medium level of adoption behaviour followed by high (28%) and low (6%) level of adoption behavior. The reasons attributable were that the technology was perceived relatively less advantageous and not observable. However, it was perceived as highly compatible, less complex and trialable. Net income of the dairy farmers had increased by Rs. 2,216.80 per dairy animal per lactation due to the adoption of TANUVAS SMART Mineral Mixture. The status of adoption of TANUVAS SMART Mineral Mixture, its adoption behaviour and change in net income were found to be significantly associated with land holding, area under fodder cultivation, dairy animal possession, extension agency contact and mass media exposure of the dairy farmers.